Correction: Modulation of subjective peripheral sensation, F-waves, and somatosensory evoked potentials in response to unilateral pinch task measured on the contractile and non-contractile sides. - Terumasa Takahara; Hidetaka Yamaguchi; Kazutoshi Seki; Sho Onodera (PLoS ONE, 2024)
[This corrects the article DOI: 10.1371/journal.pone.0261393.].